Neuron-Specific Enolase and S100B as Biomarkers of Ischemic Brain Injury During Surgery - Matej Makovec; Milan Skitek; Leja Šimnovec; Aleš Jerin (Clinics and Practice)
Biochemical markers can be used in addition to neuroimaging techniques to evaluate the extent of ischemic brain injuries and to enable earlier diagnosis and faster intervention following the ischemic event. Among the potential biomarkers of ischemic brain injuries during surgery, neuron-specific enolase (NSE) and S100B are the most frequently studied and were shown to be the most promising. The aim of this review was to summarize the role of NSE and S100B as biomarkers of ischemic brain injuries that occur during selected surgical procedures, predominantly carotid endarterectomy (CEA). Some other invasive interventions that cause ischemic brain injuries, like extracorporeal membrane oxygenation, were also included. We can conclude that these biomarkers can be useful for the evaluation of ischemic brain injuries that occur during various surgical procedures. They can help to determine the most optimal conditions for performing the surgery and therefore improve the procedures to consequently minimize brain damage caused during surgery. Because of a significant delay between sample collection and obtaining the results, they are not suitable for real-time assessment of brain injuries. Some improvement can be expected with the future development of laboratory methods. The association of the changes in NSE and S100B levels during surgery with potential consequences of ischemic brain injury have been described in numerous studies. However, even in a very homogenous group of surgical procedures like CEA, these findings cannot be summarized into a common final conclusion; therefore, the prognostic value of the two markers is not clearly supported at the present time.